From the corn laws to free trade : interests, ideas, and institutions in historical perspective - Schonhardt-Bailey, Cheryl, 1961- (MIT Press, 2006)
The overlapping and interacting forces that caused a Conservative government to repeal the protectionist Corn Laws against its own political principles and economic interests: extensive qualitative and quantitative analysis.